Combined bead polymerization and Cinchona organocatalyst immobilization by thiol–ene addition - Fredriksen, Kim A.; Kristensen, Tor E.; Hansen, Tore (Beilstein Journal of Organic Chemistry, 2012)
In this work, we report an unusually concise immobilization of Cinchona organocatalysts using thiol–ene chemistry, in which catalyst immobilization and bead polymerization is combined in a single step. A solution of azo initiator, polyfunctional thiol, polyfunctional alkene and an unmodified Cinchona-derived organocatalyst in a solvent is suspended in water and copolymerized on heating by thiol–ene additions. The resultant spherical and gel-type polymer beads have been evaluated as organocatalysts in catalytic asymmetric transformations.
Keywords: asymmetric catalysis; Cinchona derivatives; organocatalysis; polymerization; thiol–ene reaction